Effect of Probiotics on Respiratory Tract Allergic Disease and Gut Microbiota - Huang, Jinli; Zhang, Juan; Wang, Xingzhi; Jin, Zenghui; Zhang, Panpan; Su, Hui; Sun, Xin (Frontiers in Nutrition, 2022)
Allergy is a hypersensitivity reaction triggered by specific cell or antibody-mediated immune mechanisms. Allergies have increased in industrialized countries in recent decades. The rise in allergic respiratory diseases such as allergic rhinitis (AR) and allergic asthma (AA) is a potential threat to public health. Searches were conducted using PubMed, Google Scholar and Medline using the following key terms: allergic rhinitis OR asthma AND probiotics, allergic airway inflammation AND immune disorders, probiotics OR gut microbiota AND allergic disease, probiotics AND inflammatory. Studies from all years were included, specifically those published within the last 10 years. Some review articles and their reference lists were searched to identify related articles. The role of microbiota in respiratory allergic diseases has attracted more and more attention. Pieces of evidence suggested that the development of allergic diseases causes a possible imbalance in the composition of the gut microbiota. Compared to colonized mice, germ-free mice exhibit exaggerated allergic airway responses, suggesting that microbial host interactions play an important role in the development of allergic diseases. Probiotics modulate both the innate and adaptive inflammatory immune responses, often used as dietary supplements to provide health benefits in gastrointestinal disorders. Probiotics may serve as immunomodulators and activators of host defense pathways. Besides, oral probiotics can modulate the immune response in the respiratory system. Recently, studies in humans and animals have demonstrated the role of probiotic in RA and AA. To understand the characterization, microbiota, and the potential role of probiotics intervention of AA/AR, this review provides an overview of clinical features of AA and AR, probiotics for the prevention and treatment of AR, AA, changes in gut microbiota, and their mechanisms of action.